2023
DOI: 10.1002/ijc.34554
|View full text |Cite
|
Sign up to set email alerts
|

Association of kidney function with cancer incidence and its influence on cancer risk of smoking: The Japan Multi‐Institutional Collaborative Cohort Study

Abstract: The association between kidney function and cancer incidence is inconsistent among previous reports, and data on the Japanese population are lacking. It is unknown whether kidney function modifies the cancer risk of other factors. We aimed to evaluate the association of estimated glomerular filtration rate (eGFR) with cancer incidence and mortality in 55 242 participants (median age, 57 years; 55% women) from the Japan Multi-Institutional Collaborative Cohort Study. We also investigated differences in cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… Kitchlu et al (2022) found an increased risk of cancer in patients with CKD. Similarly, Kurasawa et al (2023) reported a U-shaped relationship between estimated glomerular filtration rate and cancer incidence. The FDA has previously warned about the potential risk of medullary thyroid cancer with glucagon-like peptide-1 receptor agonists.…”
Section: Discussionmentioning
confidence: 93%
“… Kitchlu et al (2022) found an increased risk of cancer in patients with CKD. Similarly, Kurasawa et al (2023) reported a U-shaped relationship between estimated glomerular filtration rate and cancer incidence. The FDA has previously warned about the potential risk of medullary thyroid cancer with glucagon-like peptide-1 receptor agonists.…”
Section: Discussionmentioning
confidence: 93%
“…The National Cancer Center's new 12 Articles on Cancer Prevention states that prevention and control of heavy drinking, smoking, and obesity are recommended [1]. Some cancers and malignancies have been determined or assumed to be caused by smoking or viruses, but some cancers are described in the paper as having no clear cause [2][3][4][5][6][7][8][9][10][11][12][13]. On the other hand, the authors initially focused on Kawasaki disease (KD) and found the epidemiological fact that "pollen may be the triggering factor for KD" in 2003, and since then, a total of four papers were reported until 2016 [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%